2018
DOI: 10.1080/15384101.2018.1496744
|View full text |Cite
|
Sign up to set email alerts
|

Kidney atrophy vs hypertrophy in diabetes: which cells are involved?

Abstract: One of the first structural changes in diabetic nephropathy (DN) is the renal enlargement. These changes resulted in renal hypertrophy in both glomerular and tubular cells. Shrink in the kidney size, which described as kidney atrophy resulted from the loss of nephrons or abnormal nephron function and lead to loss of the kidney function. On the other hand, increase in kidney size, which described as hypertrophy resulted from increase in proximal tubular epithelial and glomerular cells size. However overtime, tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 33 publications
1
24
1
1
Order By: Relevance
“…Majdan et al 4 reported that most of their type 2 diabetes mellitus patients with chronic kidney disease had small kidneys. Notably, Habib 5 proposed that both kidney hypertrophy and atrophy can occur in diabetes mellitus. The early changes in diabetic kidneys are mainly due to tubular basement membrane thickening, which leads to kidney hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Majdan et al 4 reported that most of their type 2 diabetes mellitus patients with chronic kidney disease had small kidneys. Notably, Habib 5 proposed that both kidney hypertrophy and atrophy can occur in diabetes mellitus. The early changes in diabetic kidneys are mainly due to tubular basement membrane thickening, which leads to kidney hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…The early changes in diabetic kidneys are mainly due to tubular basement membrane thickening, which leads to kidney hypertrophy. On the other hand, various tubulointerstitial diseases can induce apoptosis in proximal tubular cells, causing tubular atrophy and fibrosis and ultimately kidney atrophy 5 . Furthermore, atherosclerosis and related ischemic diseases can decrease the blood supply to the kidneys, resulting in kidney atrophy 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic kidney disease imposes structural changes to the kidney that results in altered kidney size, clinically observed as an initial hypertrophic phase [ 48 , 49 ] that is followed by later-stage atrophy [ 50 52 ]. Additionally, structural and functional changes to the kidney are observed with normal aging and this can also lead to alterations in kidney size, seen as a decrease with age that is most apparent after the age of 50 [ 53 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In physiological hypertrophy, however, the response is dominated by tubular cells without kidney damage and disease manifestation. In diabetes reactive oxygen species, increased matrix formation and insulin signalling may all contribute to the hypertrophic process, in addition to other harmful processes like including proteinuria, podocyte depletion, hyperglycaemic and hypertensive damage . Nitric oxide‐mediated endothelial dysfunction may also drive the transition from hypertrophy to kidney injury in DN .…”
Section: Compensatory Renal Hypertrophy In Humansmentioning
confidence: 99%
“…In diabetes reactive oxygen species, increased matrix formation and insulin signalling may all contribute to the hypertrophic process, in addition to other harmful processes like including proteinuria, podocyte depletion, hyperglycaemic and hypertensive damage. 33,34 Nitric oxide-mediated endothelial dysfunction may also drive the transition from hypertrophy to kidney injury in DN. 35 Recent studies have implicated reductions in autophagy, IL6/JAK2/STAT3 signalling 36 and specific micro-RNA (miRNA) molecules in the pathogenesis of diabetesinduced glomerular hypertrophy, 37 but the role for such processes and molecules in CRH is less clear.…”
Section: Pathologic Compensatory Renal Hypertrophymentioning
confidence: 99%